The preparation needs of federal inspectors of schools, Peninsular Malaysia / Sergit Singh Gurbaksh Singh - Sergit Singh, Gurbaksh Singh (1978)
In the Malaysian education system, the Federal Inspector of Schools occupies a key position in educational leadership. This study sought to determine the professional preparation needed in order to perform competently the many tasks of the Inspectorate. The discovery of the preparation needs of Inspectors was conceived in terms of two inter-related problems: (1) identifying the significance of tasks of Inspectors of Schools, and (2) determining the adequacy of their preparation for the Inspectoral role. Through the use of structured questionnaires and non-parametric statistical methods, the opinions of Federal Inspectors of School, Headmasters/Headmistresses of secondary schools, Peninsular Malaysia and selected Ministry of Education Officials were obtained on a number of topics related to the problem. Summary of Major Findings. 1. Major Tasks of Inspectors of Schools. While the three respondent groups were in general agreement on the importance and unimportance of tasks in each responsibility area, the opinions of Inspectors and other respondents showed a significant disagreement on some tasks of the Advisory and Assessment functions. This could lead to role conflicts in these tasks. 2. Relative Importance of Task Areas. The relative importance of the six task areas assigned by each respondent group showed remarkably high agreement. 3. Adequacy of Preparation. There is a clear need to develop, pilot and evaluate training materials and programmes and other experiences for Inspectors in the light of this study's findings. (i) Pre-Service preparation. The evidence showed that Federal Inspectors of Schools had received training for the teaching profession rather than specialized training for the Inspectorate. The task areas in which Inspectors felt most incompetent and their opinions on the adequacy of their pre-service preparation supported the general conclusions of inadequate preparation. (ii) In-service education. The total evidence concerning the adequacy of the inservice training programme suggested that it was not as effective as it might be and not too successful in compensating for the pre-service preparation deficiencies. Recommendations. The major recommendations arising out of this study are summarized in the following statements: 1. Recruitment and Selection. (i) Recruitment and selection procedures for the Federal Inspectorate of Schools in Peninsular Malaysia should be carefully reviewed. Particular attention should be paid in future to securing a better balance of recruits of the right calibre with experience in primary and secondary education and to the need to have within the Inspectorate some Inspectors with special knowledge of social developments affecting education. (ii) There is an urgent need to expand the Inspectorate of Schools to include more regional/state Inspectors. This would reduce the number of teachers in each Inspector's district to give the Inspector more time for professional leadership. (iii) In a job so dependent on high personal worth, personal quality should, when necessary, outweigh direct teaching/administrative experience, and such persons should be actively sought. Pre-service preparation. (i) Specialised training for the competent performance of significant tasks together with a successful internship should be a pre-requisite for future employment. (ii) There seems little doubt that a more systemmatic and effective induction procedures are desirable and necessary. In-service Preparation. (i) The present in-service training programme should be carefully evaluated - if need be, by faculty of education staff members of a local university, Ministry of Education officials and by Inspectors themselves. (ii) Considerable responsibility rests on the administration to provide conditions and opportunities that will assist and encourage Inspectors of Schools. (iii) There ought to be a special reading scheme and Inspectors encouraged to spend a reasonable amount of time each year in keeping up to date rather than performing regular duties.